Correos electrónicos y mensajes de funcionarios públicos como información pública - Morachimo Rodríguez, Miguel Enrique (2021)
The law regarding protection of public servants’ data in government-owned servers is ambiguous and could even be considered unconstitutional. The authors develop ideas with which they argue if information, messages and communications inside government-owned servers should be accessible to the public, by virtue of the right to information.